Shaping the academic productivity: Theory on the early scientific article writing among the lecturers - Fajaruddin, Syarief; Retnawati, Heri; Setiawan, Caly; Nuryana, Zalik; Bahar, Rosid; Irambona, Alfred (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
The study aims at uncovering the factors that influence the early productivity of lecturers in writing scientific articles. The main problem under review is how the early writing experience shapes the continuity of academic productivity. In conducting the study, the qualitative approach of Grounded Theory was used with the data gathered from in-depth interviews with 18 lecturers throughout Indonesia. The research participants were purposively selected and were interviewed in stages by means of theoretical sampling. Then, the data were analyzed by using ATLAS.ti, and the data validity was tested by using method and theory triangulation. The results of the study show that publication productivity does not take place naturally but is shaped through social intervention, personal strategy, technology mastery, academic literacy, reading habit, and target stipulation. These results highlight the need to foster a supportive academic ecosystem to sustain lecturers’ writing productivity over time.